1973
DOI: 10.1111/j.1476-5381.1973.tb08318.x
|View full text |Cite
|
Sign up to set email alerts
|

Central noradrenergic neurones and the cardiovascular actions of clonidine in the rabbit

Abstract: Summary1. Clonidine (1 ,ug/kg), given by intracisternal injection to anaesthetized rabbits, lowered mean arterial blood pressure by 33 mmHg and heart rate by 32 beats/min.2. In animals pre-treated with 6-hydroxydopamine (6-OHD 500 ,ug/kg intracisternally) 7-10 days before, intracisternal clonidine (1 ,ug/kg) reduced mean arterial blood pressure by only 2-5 mmHg and heart rate by 4 beats/minute.3. The hypotensive action of intravenous clonidine was reduced to 49% of control by pre-treatment with intracisternal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

1973
1973
1991
1991

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…It is possible, however, that these excitations could be mediated by a presynaptic action of clonidine. Dollery & Reid (1973) have shown that 6-hydroxydopamine, which causes a degeneration of central catecholamine-containing neurones, greatly reduces the hypotensive response to clonidine. Since an interaction with possibly dopaminergic neurones has previously been shown to be unlikely by Bolme & Fuxe (1971), the observation of Dollery & Reid (1973) suggests that clonidine may interact at least in part with the noradrenaline-releasing neurones themselves rather than with the postsynaptic receptor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible, however, that these excitations could be mediated by a presynaptic action of clonidine. Dollery & Reid (1973) have shown that 6-hydroxydopamine, which causes a degeneration of central catecholamine-containing neurones, greatly reduces the hypotensive response to clonidine. Since an interaction with possibly dopaminergic neurones has previously been shown to be unlikely by Bolme & Fuxe (1971), the observation of Dollery & Reid (1973) suggests that clonidine may interact at least in part with the noradrenaline-releasing neurones themselves rather than with the postsynaptic receptor.…”
Section: Resultsmentioning
confidence: 99%
“…Dollery & Reid (1973) have shown that 6-hydroxydopamine, which causes a degeneration of central catecholamine-containing neurones, greatly reduces the hypotensive response to clonidine. Since an interaction with possibly dopaminergic neurones has previously been shown to be unlikely by Bolme & Fuxe (1971), the observation of Dollery & Reid (1973) suggests that clonidine may interact at least in part with the noradrenaline-releasing neurones themselves rather than with the postsynaptic receptor. A reduction in the release of noradrenaline by sympathetic neurones in the presence of clonidine has been demonstrated by Starke, Wagner & Schumann (1972) and a reduced noradrenaline release from field-stimulated brain slices in the presence of clonidine by Farnebo & Hamberger (1971).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fall is preceded by a transient rise which is a peripheral effect due to vasoconstriction. But the fall is central in origin and has been obtained with minute doses of clonidine injected into the vertebral arteries (Sattler & van Zweiten, 1967;Constantine & McShane, 1968;Katic, Lavery & Lowe, 1972) into the cisterna magna (Kobinger, 1967;Kobinger & Walland, 1967; Dollery & Reid, 1973), and into the lateral or third cerebral ventricle (Schmitt, 1970). The fall is not abolished by vagotomy and is due to a decrease in sympathetic vasomotor tone.…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic action is chiefly central (Katic, Lavery & Rowe, 1972;Dollery & Reid, 1973) although there is also evidence for a peripherally mediated reduction in plasma catecholamine concentration (Brown & Harland, 1984). Clonidine also causes short-term behavioural sedation or sleep in rabbits (Gadie, McCarthy & Tulloch, 1983), chicks and rats (Holman, Shillito & Vogt, 1971).…”
Section: Introductionmentioning
confidence: 99%